Coal gangue-based solid waste microcellular foam material and preparation method thereof

Through physical foaming technology, industrial solid waste is converted into coal gangue-based solid waste microporous foaming materials, solving the problem of resource utilization of industrial solid waste and achieving efficient utilization and environmental protection effects.

CN119591377APending Publication Date: 2025-03-11HULUNBUIR UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411258179.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively utilize industrial solid waste such as coal gangue, fly ash, alkaline calcium carbide slag and desulfurization gypsum, resulting in waste of resources and environmental pollution.

Method used

Through physical foaming technology, industrial solid waste such as coal gangue, fly ash, alkaline calcium carbide slag and desulfurization gypsum is converted into coal gangue-based solid waste microporous foaming materials, and phase-change materials are used to modify coal gangue to improve the insulation performance and mechanical strength of the materials.

Benefits of technology

It realizes efficient utilization of industrial solid waste, prepares new building materials with good thermal insulation properties and mechanical strength, and reduces environmental pollution and resource waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a coal gangue-based solid waste microcellular foam material and a preparation method thereof, and relates to the technical field of thermal insulation materials. The coal gangue-based solid waste microcellular foaming material is mainly prepared from the following raw materials in parts by mass: 40 to 50 parts of coal gangue, 20 to 30 parts of phase-change material modified coal gangue, 20 to 30 parts of fly ash, 20 to 25 parts of alkali carbide slag, 5 to 10 parts of desulfurized gypsum, 0.5 to 2 parts of foaming agent, 1 to 3 parts of calcium stearate, 0.5 to 2 parts of accelerator and 0.5 to 1.5 parts of polycarboxylic acid water reducing agent. According to the invention, industrial solid wastes such as coal gangue, fly ash, alkali carbide slag, desulfurized gypsum and the like are converted into a high-performance thermal insulation material, efficient utilization of solid waste materials is realized through a physical foaming technology, and meanwhile, a novel building material with good thermal insulation performance and mechanical strength is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal insulation materials, and in particular to a gangue-based solid waste microporous foaming material and a preparation method thereof. Background Art

[0002] With the rapid development of global industrialization and urbanization, energy consumption continues to grow, especially the status of coal as the main energy source is still irreplaceable in many countries. However, the mining and utilization of coal produces a large amount of solid waste, one of which is coal gangue. Coal gangue is waste generated during coal mining, mainly composed of minerals in coal, including silicon, aluminum, iron and other elements. For a long time, the treatment of coal gangue has been a major environmental problem faced by mining areas and the entire society.

[0003] Traditional methods of treating coal gangue mainly include stacking and landfilling, which not only occupy a large amount of land resources, but also easily cause environmental pollution, such as heavy metal pollution and dust pollution. In addition, the useful components in coal gangue are not reasonably utilized, resulting in a huge waste of resources. Therefore, exploring ways to utilize coal gangue as a resource is of great significance to promoting sustainable development.

[0004] Fly ash is the fine ash collected from the flue gas after coal combustion. It is one of the main solid wastes discharged by coal-fired power plants. With the rapid development of China's energy industry, the emission of fly ash has increased sharply, which has put great pressure on China's national economic construction and ecological environment.

[0005] Alkali carbide slag mainly comes from the distillation recovery process of the ammonia-soda process, especially the solid residue produced in the process of treating ammonia filtrate and lime milk. The accumulated and discharged alkali carbide slag not only occupies a large amount of land, but also the harmful components in it easily penetrate into the soil and groundwater, causing serious pollution. Its fine particles are also easily inhaled by the human body, which is harmful to health. At present, the utilization rate of alkali carbide slag in China is only 3% to 4%. Although a variety of utilization ideas have been proposed, such as damming and land reclamation, they have not been widely used.

[0006] Desulfurization gypsum is an industrial by-product obtained by desulfurization and purification of flue gas produced by coal combustion. Although it has broad application potential in many fields, its resource utilization still faces many difficulties and has not been used on a large scale.

[0007] In the field of building materials, the demand for thermal insulation materials is growing. Although traditional thermal insulation materials such as polystyrene boards and extruded boards have good thermal insulation properties, most of them are based on petrochemical products, which not only consume non-renewable resources, but also may release harmful substances during use, posing a potential threat to the environment and human health. Therefore, the development of new environmentally friendly and efficient thermal insulation materials has become an important research direction in this field.

[0008] Coal gangue, fly ash, alkali carbide slag, desulfurized gypsum, etc. are solid wastes generated in industrial processes. These solid wastes also have treatment difficulties, and due to their huge emissions, their environmental impact is becoming increasingly prominent. How to effectively utilize these industrial solid wastes and turn them into treasures is one of the current research hotspots.

[0009] In view of the above-mentioned deficiencies in the existing technology, the development of a new technology that can not only efficiently utilize industrial solid wastes such as coal gangue, fly ash, alkali carbide slag, and desulfurization gypsum, but also prepare thermal insulation materials with excellent performance has important practical significance for realizing the resource utilization of industrial solid wastes, reducing environmental pressure, and promoting the green development of the building materials industry. Summary of the invention

[0010] The present invention aims to provide a gangue-based solid waste microporous foaming material and a preparation method thereof, which can convert industrial solid wastes such as gangue, fly ash, alkali carbide slag, desulfurized gypsum, etc. into high-performance thermal insulation materials. Through physical foaming technology, efficient utilization of solid waste materials is achieved, and a new type of building material with good thermal insulation performance and mechanical strength is prepared.

[0011] The gangue-based solid waste microporous foaming material is mainly composed of the following raw materials, calculated by weight: 40-50 parts of gangue, 20-30 parts of phase change material modified gangue, 20-30 parts of fly ash, 20-25 parts of alkali carbide slag, 5-10 parts of desulfurized gypsum, 0.5-2 parts of foaming agent, 1-3 parts of calcium stearate, 0.5-2 parts of accelerating setting agent and 0.5-1.5 parts of polycarboxylic acid water reducer.

[0012] Gangue and fly ash are used as the main raw materials to provide silicon and aluminum components; alkali carbide slag is used as an alkaline activator, and desulfurized gypsum is used as a sulfate activator, which work together to stimulate the activity of gangue and fly ash to generate cementitious substances such as hydrated calcium silicate and hydrated calcium aluminate, thereby improving the strength of the material; the phase change temperature range and energy storage capacity of the phase change material modified gangue are adjusted as needed to improve the heat storage and regulation capacity of the thermal insulation material; the foaming agent produces uniform and independent bubbles inside the material to form a microporous structure and reduce the bulk density of the material; calcium stearate is used as a foam stabilizer to stabilize the generated bubbles and prevent them from bursting; the accelerator adjusts the setting time to make the slurry lose fluidity quickly and fix the bubbles; the polycarboxylic acid water reducer reduces the water consumption, reduces the capillaries generated by water evaporation, and improves the mechanical properties of the product.

[0013] Preferably, the phase change material modified coal gangue is prepared by the following method: S1, grinding the coal gangue, calcining and activating it, acid leaching it and then drying it to obtain pretreated coal gangue powder; S2, immersing the pretreated coal gangue powder in a phase change material solution; S3. Take out the coal gangue in step S2, coat it with polyvinyl alcohol, and then dry it to obtain phase change material modified coal gangue.

[0014] Preferably, in step S1, the calcination temperature is 780-820°C and the duration is 2.5-3 hours. If the temperature is too low, the activation is insufficient; if the temperature is too high, the pore size is too large, which affects the subsequent coating sealing, and if the pore size is too large, the strength of the material is affected.

[0015] Preferably, in step S1, the particle size of the finely ground coal gangue is 1-1.5 mm.

[0016] Preferably, in step S1, the acid leaching is performed by immersing in hydrochloric acid with a concentration of 10wt% to 20wt% for 30 to 60 minutes.

[0017] Preferably, in step S2, the impregnation specifically comprises the following steps: pre-treating the gangue by immersing it in a phase change material solution at 50-55°C under vacuum for 1.5-3 h, and then ultrasonicating the mixture at 55-65°C for 1.5-3 h.

[0018] Preferably, in step S2, the mass ratio of the coal gangue powder to the phase change material is 0.5-0.8:1.

[0019] Preferably, in step S2, the phase change material is a fatty acid phase change material.

[0020] Further preferably, the fatty acid phase change material includes capric acid phase change material, lauric acid phase change material, capric acid and lauric acid eutectic mixture phase change material, myristic acid phase change material, capric acid and stearic acid eutectic mixture phase change material or lauric acid and palmitic acid eutectic mixture phase change material.

[0021] Preferably, in step S3, the mass ratio of the polyvinyl alcohol to the coal gangue powder is 1-1:1.5.

[0022] Preferably, the foaming agent includes sodium rosin acid, alkyl sulfonate, sodium fatty alcohol sulfate, sodium tripolyphosphate or sodium dodecyl sulfate.

[0023] Compared with the prior art, the beneficial effects of the present invention are: 1. The present invention converts industrial solid wastes such as coal gangue, fly ash, alkali carbide slag, desulfurized gypsum, etc. into high-performance thermal insulation materials, thereby achieving efficient utilization of solid waste materials and preparing new building materials with good thermal insulation performance and mechanical strength.

[0024] 2. The thermal insulation material prepared by the present invention after modifying coal gangue can adjust the phase change temperature range and energy storage capacity of the modified coal gangue as needed, thereby improving the heat storage and regulation capabilities of the thermal insulation material. DETAILED DESCRIPTION

[0025] The technical scheme of the present invention is further described below by way of examples. The raw materials used in the examples can be purchased from the market or prepared by conventional methods.

[0026] Example 1 A coal gangue-based solid waste microporous foaming material is mainly composed of the following raw materials, measured by mass: 400 g of coal gangue, 200 g of phase change material modified coal gangue, 300 g of fly ash, 200 g of alkali carbide slag, 150 g of desulfurized gypsum, 5 g of sodium rosin acid, 20 g of calcium stearate, 10 g of accelerator and 15 g of polycarboxylic acid water reducer.

[0027] The phase change material modified coal gangue is prepared as follows: S1. Grind the coal gangue, activate it by calcination, acid-leach it and then dry it to obtain pretreated coal gangue powder; the particle size of the finely ground coal gangue is 1-1.5 mm; the calcination temperature is 800 °C and the duration is 3 h; the acid-leach is specifically soaked in a 10wt% hydrochloric acid solution under stirring conditions for 1 h.

[0028] S2. The pretreated gangue is immersed in the capric acid phase change material solution at 60 °C under vacuum for 2 h, and then the mixture is ultrasonicated at 55 °C for 1.5 h; the mass ratio of the gangue powder to the phase change material is 0.5-0.8:1 S3. Take out the coal gangue in step S2, and coat it with polyvinyl alcohol in a mass ratio of polyvinyl alcohol to coal gangue powder of 1:1, and obtain phase change material modified coal gangue after drying.

[0029] The preparation method of the gangue-based solid waste microporous foam material is as follows: P1, 400 g of coal gangue, 200 g of phase change material modified coal gangue, 300 g of fly ash, 200 g of alkali carbide slag, 150 g of desulfurized gypsum, 20 g of calcium stearate, 15 g of polycarboxylate water reducer and 400 g of water were mixed and stirred to obtain a mixed slurry; P2. Mix 5 g of sodium rosinate, 10 g of accelerator and 40 g of water, and use an air compressor to inject compressed air to prepare a foaming solution until the volume of the foaming solution is equivalent to the volume of the mixed slurry; P3. Add the bubble solution obtained in step P2 to the mixed slurry in step P1 and mix them evenly; obtain the gangue-based solid waste microporous foaming material.

[0030] Example 2 A coal gangue-based solid waste microporous foaming material is mainly composed of the following raw materials, measured by mass: 400 g of coal gangue, 250 g of phase change material modified coal gangue, 250 g of fly ash, 200 g of alkali carbide slag, 150 g of desulfurized gypsum, 20 g of sodium rosin acid, 20 g of calcium stearate, 10 g of accelerator and 15 g of polycarboxylic acid water reducer.

[0031] The phase change material modified coal gangue is prepared as follows: S1. Grind the coal gangue, activate it by calcination, acid-leach it and then dry it to obtain pretreated coal gangue powder; the particle size of the finely ground coal gangue is 1-1.5 mm; the calcination temperature is 800 °C and the duration is 3 h; the acid-leach is specifically soaked in a 10wt% hydrochloric acid solution under stirring conditions for 1 h.

[0032] S2. The pretreated gangue is immersed in the capric acid phase change material solution at 60 °C under vacuum for 2 h, and then the mixture is ultrasonicated at 55 °C for 1.5 h; the mass ratio of the gangue powder to the phase change material is 0.5-0.8:1 S3. Take out the coal gangue in step S2, and coat it with polyvinyl alcohol in a mass ratio of polyvinyl alcohol to coal gangue powder of 1:1, and obtain phase change material modified coal gangue after drying.

[0033] The preparation method of the gangue-based solid waste microporous foam material is as follows: P1, 400 g of coal gangue, 250 g of phase change material modified coal gangue, 250 g of fly ash, 200 g of alkali carbide slag, 150 g of desulfurized gypsum, 20 g of calcium stearate, 15 g of polycarboxylate water reducer and 400 g of water were mixed and stirred to obtain a mixed slurry; P2. Mix 20 g of sodium rosin acid, 10 g of accelerator and 70 g of water, and use an air compressor to inject compressed air to prepare a foaming solution until the volume of the foaming solution is equivalent to the volume of the mixed slurry; P3. Add the bubble solution obtained in step P2 to the mixed slurry in step P1 and mix them evenly; obtain the gangue-based solid waste microporous foaming material.

[0034] Example 3 A coal gangue-based solid waste microporous foaming material is mainly composed of the following raw materials, measured by mass: 400 g of coal gangue, 300 g of phase change material modified coal gangue, 200 g of fly ash, 200 g of alkali carbide slag, 150 g of desulfurized gypsum, 10 g of sodium rosin acid, 20 g of calcium stearate, 10 g of accelerator and 15 g of polycarboxylic acid water reducer.

[0035] The phase change material modified coal gangue is prepared as follows: S1. Grind the coal gangue, activate it by calcination, acid-leach it and then dry it to obtain pretreated coal gangue powder; the particle size of the finely ground coal gangue is 1-1.5 mm; the calcination temperature is 800 °C and the duration is 3 h; the acid-leach is specifically soaked in a 10wt% hydrochloric acid solution under stirring conditions for 1 h.

[0036] S2. The pretreated gangue is immersed in the capric acid phase change material solution at 60 °C under vacuum for 2 h, and then the mixture is ultrasonicated at 55 °C for 1.5 h; the mass ratio of the gangue powder to the phase change material is 0.5-0.8:1 S3. Take out the coal gangue in step S2, and coat it with polyvinyl alcohol in a mass ratio of polyvinyl alcohol to coal gangue powder of 1:1, and obtain phase change material modified coal gangue after drying.

[0037] The preparation method of the gangue-based solid waste microporous foam material is as follows: P1, 400 g of coal gangue, 300 g of phase change material modified coal gangue, 200 g of fly ash, 200 g of alkali carbide slag, 150 g of desulfurized gypsum, 20 g of calcium stearate, 15 g of polycarboxylate water reducer and 400 g of water were mixed and stirred to obtain a mixed slurry; P2. Mix 10 g of sodium rosin acid, 10 g of accelerator and 50 g of water, and use an air compressor to inject compressed air to prepare a foaming solution until the volume of the foaming solution is equivalent to the volume of the mixed slurry; P3. Add the bubble solution obtained in step P2 to the mixed slurry in step P1 and mix them evenly; obtain the gangue-based solid waste microporous foaming material.

[0038] Example 4 A coal gangue-based solid waste microporous foaming material is mainly composed of the following raw materials, measured by mass: 500 g of coal gangue, 300 g of phase change material modified coal gangue, 200 g of fly ash, 250 g of alkali carbide slag, 100 g of desulfurized gypsum, 10 g of sodium rosin acid, 20 g of calcium stearate, 10 g of accelerator and 15 g of polycarboxylic acid water reducer.

[0039] The phase change material modified coal gangue is prepared as follows: S1. Grind the coal gangue, activate it by calcination, acid-leach it and then dry it to obtain pretreated coal gangue powder; the particle size of the finely ground coal gangue is 1-1.5 mm; the calcination temperature is 800 °C and the duration is 3 h; the acid-leach is specifically soaked in a 10wt% hydrochloric acid solution under stirring conditions for 1 h.

[0040] S2. The pretreated gangue is immersed in the capric acid phase change material solution at 60 °C under vacuum for 2 h, and then the mixture is ultrasonicated at 55 °C for 1.5 h; the mass ratio of the gangue powder to the phase change material is 0.5-0.8:1 S3. Take out the coal gangue in step S2, and coat it with polyvinyl alcohol in a mass ratio of polyvinyl alcohol to coal gangue powder of 1:1, and obtain phase change material modified coal gangue after drying.

[0041] The preparation method of the gangue-based solid waste microporous foam material is as follows: P1. 500 g of coal gangue, 300 g of phase change material modified coal gangue, 200 g of fly ash, 250 g of alkali carbide slag, 100 g of desulfurized gypsum, 20 g of calcium stearate, 15 g of polycarboxylate water reducer and 400 g of water were mixed and stirred to obtain a mixed slurry; P2. Mix 10 g of sodium rosin acid, 10 g of accelerator and 50 g of water, and use an air compressor to inject compressed air to prepare a foaming solution until the volume of the foaming solution is equivalent to the volume of the mixed slurry; P3. Add the bubble solution obtained in step P2 to the mixed slurry in step P1 and mix them evenly; obtain the gangue-based solid waste microporous foaming material.

[0042] Comparative Example 1 A coal gangue-based solid waste microporous foaming material is mainly composed of the following raw materials in terms of mass fractions: 400 g of coal gangue, 300 g of fly ash, 200 g of alkali carbide slag, 150 g of desulfurized gypsum, 10 g of sodium rosin acid, 20 g of calcium stearate, 10 g of accelerator and 15 g of polycarboxylate water reducer.

[0043] The preparation method of the gangue-based solid waste microporous foam material is as follows: P1. Mix 400 g of coal gangue, 300 g of fly ash, 200 g of alkali carbide slag, 150 g of desulfurized gypsum, 20 g of calcium stearate, 15 g of polycarboxylate water reducer and 400 g of water to obtain a mixed slurry; P2. Mix 10 g of sodium rosin acid, 10 g of accelerator and 50 g of water, and use an air compressor to inject compressed air to prepare a foaming solution until the volume of the foaming solution is equivalent to the volume of the mixed slurry; P3. Add the bubble solution obtained in step P2 to the mixed slurry in step P1 and mix them evenly; obtain the gangue-based solid waste microporous foaming material.

[0044] Detection and analysis The foaming solutions in Examples 1 to 4 and Comparative Example 1 were respectively added to the mixed slurry, mixed evenly and then uniformly injected into a 100 mm×100 mm×100 mm mold. The mold was demolded after 24 hours of molding, and the demolded sample was placed in a standard curing box with a temperature of 20±2°C and a relative humidity of>95% for 28 days to obtain a test sample.

[0045] Determination of compressive strength: According to the compressive strength test in GB / T50081-2019 "Standard for New Test Methods for Physical and Mechanical Properties of Concrete", the compressive strength of the test samples prepared in Examples 1 to 4 and Comparative Example 1 was tested.

[0046] Thermal conductivity test: Place one side of the test sample close to the heater at 40°C in an environment with a temperature of 23°C and a humidity of 60%. Measure the time required for the temperature of the center point of the test sample relative to the heating surface to reach 40°C.

[0047] Determination of thermal conductivity: The test objects are the test samples prepared in Examples 1 to 4 and Comparative Example 1, and the thermal conductivity is tested using YB / T4130-2018 "Test method for thermal conductivity of refractory materials".

[0048] Before conducting the above tests, the test samples were placed in an environment with a temperature of 23 °C and a humidity of 60% for 24 h.

[0049] Table 1 Main component dosage in each example

[0050] Table 2 Performance test results of gangue-based solid waste microporous foam materials in various embodiments

[0051] The longer the heat conduction time, the better the thermal insulation performance of the material.

[0052] It can be seen from Examples 1 to 3 that as the content of phase change material modified coal gangue increases, the thermal insulation of the material increases, but the compressive strength decreases. Compared with Example 3, Example 4 reduces the amount of fly ash and desulfurized gypsum, increases the amount of alkali carbide slag and coal gangue, and the compressive strength decreases slightly, while the thermal insulation remains basically unchanged. Compared with Example 1, Comparative Example 1 does not add phase change material modified coal gangue, and its compressive strength is slightly improved, but the thermal insulation is significantly reduced.

[0053] It should be understood that the above embodiments are only used to illustrate the present invention and are not used to limit the scope of protection of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims of the present application.

Claims

1. A gangue-based solid waste microporous foam material, characterized in that: Calculated by mass, it is mainly composed of the following raw materials: 40-50 parts of coal gangue, 20-30 parts of phase change material modified coal gangue, 20-30 parts of fly ash, 20-25 parts of alkali carbide slag, 5-10 parts of desulfurized gypsum, 0.5-2 parts of foaming agent, 1-3 parts of calcium stearate, 0.5-2 parts of accelerator and 0.5-1.5 parts of polycarboxylic acid water reducer.

2. The gangue-based solid waste microporous foam material according to claim 1, characterized in that: The foaming agent includes sodium rosin acid, alkyl sulfonate, sodium fatty alcohol sulfate, sodium tripolyphosphate or sodium lauryl sulfate.

3. The gangue-based solid waste microporous foam material according to claim 1, characterized in that: The phase change material modified coal gangue is prepared as follows: S1, grinding the coal gangue, calcining and activating it, acid leaching it and then drying it to obtain pretreated coal gangue powder; S2, immersing the pretreated coal gangue powder in a phase change material solution; S3. Take out the coal gangue in step S2, coat it with polyvinyl alcohol, and then dry it to obtain phase change material modified coal gangue.

4. The gangue-based solid waste microporous foam material according to claim 3, characterized in that: In step S1, the calcination temperature is 780-820°C and the calcination time is 2.5-3 h.

5. The gangue-based solid waste microporous foam material according to claim 3, characterized in that: In step S1, the particle size of the finely ground coal gangue is 1-1.5 mm.

6. The gangue-based solid waste microporous foam material according to claim 3, characterized in that: In step S2, the impregnation specifically includes the following steps: impregnating the pretreated coal gangue in the phase change material solution at 50-55°C under vacuum conditions for 1.5-3 h, and then ultrasonicating the mixture at 55-65°C for 1.5-3 h.

7. The gangue-based solid waste microporous foam material according to claim 3, characterized in that: In step S2, the mass ratio of the coal gangue powder to the phase change material is 0.5-0.8:

1.

8. The gangue-based solid waste microporous foam material according to claim 3, characterized in that: In step S2, the phase change material is a fatty acid phase change material.

9. The gangue-based solid waste microporous foam material according to claim 8, characterized in that: The fatty acid phase change material includes capric acid phase change material, lauric acid phase change material, capric acid and lauric acid eutectic mixture phase change material, myristic acid phase change material, capric acid and stearic acid eutectic mixture phase change material or lauric acid and palmitic acid eutectic mixture phase change material.

10. The gangue-based solid waste microporous foam material according to claim 3, characterized in that: In step S3, the mass ratio of the polyvinyl alcohol to the coal gangue powder is 1-1:1.5.

Citation Information

Cited By

  • Anti-bleeding and high-rheology coal gangue grouting filling material as well as preparation method and application thereof

    CN122233671A